Perencanaan Pengadaan Sanitasi Lingkungan di Taman Nasional Bromo Tengger Semeru dengan Pendekatan Sanitasi Total Berbasis Masyarakat - Jamhuri, Mohammad; Sujarwo, Imam; Alisah, Evawati (JRCE (Journal of Research on Community Engagement), 2020)
Bromo Tengger Semeru National Park (TNBTS) is one of Indonesia’s premier tourist destinations, experiencing surging visitor numbers each year. During peak hours—especially early morning for sunrise—tourists flock to popular spots such as Penanjakan, Seruni, Mentingen, Kingkong, and Bukit Cinta, often causing long queues at toilet facilities. This community service program aimed to (1) identify sanitation needs in critical TNBTS locations, (2) propose additional sanitation facilities where required, and (3) conduct community mentoring to ensure sustainable involvement in facility planning and management. The methods included field surveys, queueing analysis, visitor forecasting, water requirement and cost calculations, and a Community-Based Total Sanitation (STBM) approach for local empowerment.Results indicate a need for more toilet units at several sunrise viewpoints and in the jeep and motorcycle parking areas. Queueing analysis suggests that to maintain waiting times under one minute per person at high-traffic spots, at least nine toilets for men and thirteen for women are necessary. Economic feasibility calculations reveal potential for self-financing through toilet fees, since visitor numbers are projected to rise above one million annually within five years. Community mentoring is crucial for collaborative efforts and shared ownership among local managers, residents, and relevant government agencies, thereby ensuring the facilities’ long-term sustainability.